Evaluasi Pelaksanaan Kebijakan Kampus Merdeka: Studi pada Program Magang dan Studi Independen Bersertifikat (MSIB) - Abdul Rahman; Mawar Mawar; Evi Satispi; Intan Setyaningrum (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2023)
The purpose of this study is to investigate how to evaluate the implementation of the Independent Campus policy, with a focus on the Independent Campus on the Certified Internship and Independent Study (MSIB) program. This study uses a descriptive method combined with a qualitative approach. This research found that the implementation of the Independent Campus policy, as studied in the MSIB Program is well enough and smoothly in general. This is supported by the fact that the vast majority (73%) of participants expressed satisfaction with the MSIB program's implementation thus far. As a result, 84.5% of participants thought the MSIB program was worthy of recommending to other students.Â  However, there are still challenges, such as collecting administration and student files and obtaining approval for the recognition of 20 credits. Based on these findings, the study suggests that the Ministry of Education, Culture Research, and Technology should be collaborate more closely with campuses, so that the preparation of student administration files can be supported by campuses and students can obtain 20 credit recognition rights.